EFL Teachers’ Problem in Teaching English using 2013 Curriculum at SMP Kota Ternate - Amrin Hi. Saban; Masria Kasim (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2021)
This research is to find out the problem of English teachers in using the 2013 curriculum in several schools in south ternate city. This is done to find out how English teachers can overcome the problems faced in using the 2013 curriculum from the preparation of RPP to strategies in teaching English, problems and solutions encountered in the implementation of teaching and learning process. The subjects of this study were the English teacher SMP 1 Muhammadiyah and SMP Nasional Banau. The researcher used descriptive qualitative to analyzing data. The researcher collected data by interviewing several English teachers at school and documenting some important data that support this research. Data collected from the interview script. Data analysis techniques are data reduction, data analysis,data presentation, and drawing conclusions. The result of research shown that English teachers still do not understand the 2013 curriculum with same reasons, they are; It is still difficulties in preparing RPP , the 2013 curriculum has too many assessments and the 2013 curriculum has a lot of work.